THE IMPACT OF SECURITY FACTOR ON FOREIGN DIRECT INVESTMENT INFLOW INTO ACEH BESAR DISTRICT - Abdul Hakim; Azhari Yahya (Fakultas Hukum Universitas Syiah Kuala, 2020)
The purpose of this research are to understand the impact of security factors on foreign direct investment inflow into Aceh Besar District, to find out the problems caused by security factor related to Foreign Direct Investment and to find out the obligations of the governments of Aceh Besar District in protecting foreign investors. The research use empirical approach. The results of this study found that it was the task of the regional government to protect the security for foreign investors in Aceh Besar District. The Government of Aceh Besar has several obligations to provide security factors to foreign investors as a mandate in several laws and regulations, such as providing the certainty rights, law and protection, transparent information, and facilities for the investors. It is suggested to the government of Aceh Besar pay more attention to security factors for foreign investors. The Government of Aceh Besar must provide maximum services to foreign investors so that foreign investors feel safe and comfortable in investing in Aceh Besar District. The Government of Aceh Besar must also educate the public about the importance of foreign investors for regional economic income and to open up more employment opportunities for the people of Aceh Besar District.Keywords : Aceh Besar, Foreign Direct Investment, Security Factor.